Merging Visible‐Light Photoredox and Organoamine Catalysis for the C‐3 Difluoroalkylation of Quinoxalin‐2(1H)‐Ones. Issue 8 (4th July 2019) - Jin, Can; Zhuang, Xiaohui; Sun, Bin; Li, Deyu; Zhu, Rui
Abstract: A mild and efficient protocol for visible‐light and organoamine cocatalyzed difluoroalkylation of quinoxalin‐2(1 H )‐ones with functionalized difluoromethyl bromides has been developed. The transformation could be carried out at room temperature and gave a variety of C‐3 difluoroalkylated quinoxaline‐2(1 H )‐ones in moderate to excellent yields. Moreover, mechanistic studies revealed that this transformation proceeded through a radical‐type debrominative coupling process with only need of catalytic amount of diisopropylethylamine (DIPEA). This strategy featured wide functional group tolerance, excellent regioselectivity, mild conditions, and operational simplicity. Abstract : Two PEAs in a pod : A practical protocol for photoredox and organoamine cocatalyzed regioselective difluoroalkylation of quinoxalin‐2(1 H )‐ones with difluoromethyl bromides has been developed. The reaction had a broad substrate scope and functional group tolerance, as well as excellent regioselectivity.